Analysis of tensile-shear strength of single and multi-friction stir spot welding joints under fixed welding process conditions - Hamed Haddad Khodaparast (Proceedings of the Institution of Mechanical Engineers, Part C: Journal of Mechanical Engineering Science, 2020)
The tensile-shear strength of AA 5052 single and multi-friction stir spot welding joints were analyzed using experimental, numerical, and analytical approaches. Benchmark specimens were designed and manufactured in a similar manner with respect to industrial practice. Under the fixed welding process condition, the failure mechanism of friction stir spot welded specimens under tensile-shear loading was first determined by using macro- and micro-structural analysis. It is shown that increasing the tool shoulder diameter and the number of friction stir spot weldings may nonproportionally increase the strength of the joints. In the linearly arranged multi-friction stir spot welding joints, the strength of these joints was discussed using analytical approach. It is demonstrated that in certain cases, increasing the nugget diameter is preferred than increasing the number of nuggets. This is only applicable to a certain friction stir spot welding failure mechanism. A finite element model prediction tool was developed to predict the tensile-shear strength of friction stir spot welded joints using the material properties obtained from the measurement of experimental hardness.